Process elimination underlies ontogenetic change in the distribution of callosal projection neurons in the postcentral gyrus of the fetal rhesus monkey. - Chalupa, L M (1989)
During fetal development, the regional distribution of callosal projection neurons in the rhesus monkey's postcentral gyrus changes from a uniform to a discontinuous pattern. To determine if this developmental change reflects the retraction of transient callosal projections, two different fluorescent tracers were injected into the brain of fetal monkeys of known gestational ages. Fast blue was injected into the entire postcentral gyrus of one hemisphere, whereas a second tracer (rhodamine latex beads or diamidino yellow) was injected into the caudal portion of the postcentral gyrus of the other hemisphere. The rostral portion of the postcentral gyrus (contralateral to the hemisphere injected with fast blue) was subsequently examined for the presence of labeled cells. In animals injected early in fetal development, on embryonic day 110 or younger and sacrificed 4 weeks later, there were numerous cells labeled with both tracers. In contrast, very few double-labeled cells were found in fetuses injected at an older age, embryonic day 135. We interpret these findings as showing that early in fetal development, when callosal projection neurons in the postcentral gyrus show a continuous distribution pattern, single cells in the rostral portion of this gyrus possess at least two collaterals, one projecting to the contralateral hemisphere and the other to the caudal portion of the gyrus. Subsequently, many of these neurons retract callosal collaterals while maintaining ipsilateral projections. Thus, process elimination accounts for the establishment of the discontinuous distribution of callosal neurons found in the postcentral gyrus of the mature primate.